2022
DOI: 10.1111/gcb.16171
|View full text |Cite
|
Sign up to set email alerts
|

Climate oscillations drive millennial‐scale changes in seabird colony size

Abstract: Seabird population size is intimately linked to the physical, chemical, and biological processes of the oceans. Yet, the overall effects of long‐term changes in ocean dynamics on seabird colonies are difficult to quantify. Here, we used dated lake sediments to reconstruct ~10,000‐years of seabird dynamics in the Northwest Atlantic to determine the influences of Holocene‐scale climatic oscillations on colony size. On Baccalieu Island (Newfoundland and Labrador, Canada)—where the world's largest colony of Leach'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…This method mainly adds a fundamental step in the use of GAMMs in time series analysis, which is the calculation of first derivatives that highlight periods of change in the modelled non-linear relationships. This method is readapted here to study how bird response changes over time, representing the first application of this method in studies of animal behaviour after it was recently used in climate and paleoclimatic change studies [46, 51, 52]. This methodology allowed us to explore whether bird flight behaviour modification as the circulation of the wind varies over time.…”
Section: Discussionmentioning
confidence: 99%
“…This method mainly adds a fundamental step in the use of GAMMs in time series analysis, which is the calculation of first derivatives that highlight periods of change in the modelled non-linear relationships. This method is readapted here to study how bird response changes over time, representing the first application of this method in studies of animal behaviour after it was recently used in climate and paleoclimatic change studies [46, 51, 52]. This methodology allowed us to explore whether bird flight behaviour modification as the circulation of the wind varies over time.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were expected to have resulted in increased predation on Leach's Storm-petrels by gulls, as they sought to bridge the nutritional gap between chicks hatching, and capelin spawning Montevecchi 1999, Stenhouse et al 2000). Though oceanographic and climatic conditions are strong drivers of Leach's Storm-petrel populations, anthropogenic influences are increasingly important (Duda et al 2022). Initial estimates in 1997 found that 49,000 storm-petrels were depredated annually on Great Island, raising concerns for the storm-petrel population's persistence (Stenhouse et al 2000).…”
Section: Introductionmentioning
confidence: 99%